2023
DOI: 10.3390/pharmaceutics15092244
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin Modified Hydrogels of Kappa-Carrageenan for Methotrexate Delivery

Maria Nikitina,
Nataliya Kochkina,
Marianna Arinina
et al.

Abstract: This work is aimed at developing a kappa-carrageenan (kCR) gel with increased methotrexate (MTX) content. β-Cyclodextrin (βCD), which is able to inclusion complex formation with MTX, has been used to increase the drug concentration in the hydrogel. The rheological behavior of the designed gels was investigated and the influence of MTX and βCD on the viscoelastic properties of kCR gel was studied in detail. The effect of βCD and its concentration on the MTX-releasing rate from the kCR gels was examined. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Similarly, Zarbab et al reported guar gum/chitosan/PVA hydrogels cross-linked with tetra orthosilicate hydrogels; 96% MTX was released in 7 h and 25 min in PBS at pH 7.4 for the treatment of colon cancer [ 54 ]. Nikitina et al developed k-CG/MTX and k-CG/ β -cyclodextrin hydrogels which showed 65% and 100% MTX released in 6 h in PBS at pH 7.4, respectively [ 55 ]. Fe 3 O 4 -incorporated k-CG/chitosan hydrogels were reported by Mahdavinia et al .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Zarbab et al reported guar gum/chitosan/PVA hydrogels cross-linked with tetra orthosilicate hydrogels; 96% MTX was released in 7 h and 25 min in PBS at pH 7.4 for the treatment of colon cancer [ 54 ]. Nikitina et al developed k-CG/MTX and k-CG/ β -cyclodextrin hydrogels which showed 65% and 100% MTX released in 6 h in PBS at pH 7.4, respectively [ 55 ]. Fe 3 O 4 -incorporated k-CG/chitosan hydrogels were reported by Mahdavinia et al .…”
Section: Resultsmentioning
confidence: 99%